Analisis Determinan Harga Saham Perusahaan Sektor Agriculture Yang Terdaftar Di Bursa Efek Indonesia - Puja Rizqy Ramadhan; Dito Aditia Darma Nasution (Jurnal Riset Akuntansi dan Bisnis, 2020)
This research was conducted to find out how the influence of return on assets, earnings per share, and debt to asset ratio on stock prices in agriculture sector companies listed on the Indonesia Stock Exchange. The population in this research amounted to 21 agricultural companies with a sample of 18 companies. This research used secondary data taken from idx.co.id with data used from 2014-2018. This research used quantitative data with multiple linear regression models. The results showed that the return on assets and debt to assets ratio partially had a negative and significant effect on the stock prices of agriculture companies, while the earnings per share had a positive and significant effect on the prices of shares of agriculture companies. Simultaneous return on assets, earnings per share, and debt to asset ratios had a significant effect on the prices of agricultural companies Return on assets, earnings per share and debt to asset ratio contributed 82.3% in the formation of stock prices, while the remaining 17.7% was obtained from other factors. Stock prices had a very close relationship to return on assets, earnings per share, and debt to asset ratio.